2019
DOI: 10.18203/issn.2455-4529.intjresdermatol20190481
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in psoriasis: a clinical study

Abstract: <p class="abstract"><strong>Background:</strong> Psoriasis is a common inflammatory dermatosis with a chronic course that can have a significant detrimental effect on the quality of life (QoL) of those suffering from it. We conducted this study to evaluate the effect of psoriasis on QoL and to assess the impact of demographic factors and disease severity on QoL.</p><p class="abstract"><strong>Methods:</strong> Ninety patients attending the Dermatology OPD at Himalayan … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…The result of this study showed female gender was found to be independent predictors, which increases the chance of having poor quality of life. This was supported by a similar study done in India [30], the United States of America [31], Spain [32]. The probable reason could be the fact that females are more concerned about their body image and physical appearance than their male counterparts and they are more likely to feel troubled in public settings.…”
Section: Discussionsupporting
confidence: 61%
“…The result of this study showed female gender was found to be independent predictors, which increases the chance of having poor quality of life. This was supported by a similar study done in India [30], the United States of America [31], Spain [32]. The probable reason could be the fact that females are more concerned about their body image and physical appearance than their male counterparts and they are more likely to feel troubled in public settings.…”
Section: Discussionsupporting
confidence: 61%
“…The result of this study showed female gender was found to be independent predictors, which increases the chance of having poor QoL. This was supported by similar studies done in India [32], the United States of America [33], and Spain [34]. The probable reason could be the fact that females are more concerned about their body image and physical appearance than their male counterparts and they are more likely to feel troubled in public settings.…”
Section: Plos Onesupporting
confidence: 80%
“…[ 14 17 ] In contrast, a cross–sectional observational study from India found that PsO had a very-large effect on QoL in 70% of patients. [ 18 ] A prospective observational study from India including 154 patients with PsO found that 90.3% patients had depression. [ 14 ] Age, marital status, educational status, working status, and severity of PsO were significantly impacting depression in these patients.…”
Section: Discussionmentioning
confidence: 99%